Development of drilling well irrigation to meet water needs in the rainfall of Sambirejo village, Kabupaten Langkat (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
One very important element in agriculture is water. The availability of water must be guaranteed so that plants can grow throughout the year. The lack of water availability means that crops cannot be produced throughout the year, causing farmers to become inadequate. Engineering irrigation is one of the systems that can regulate water availability throughout the year, but not all regions in Indonesia have such irrigation. Sambirejo Village is one of the villages in Langkat Regency which still utilizes a rainfed irrigation system. The main problem from Sambirejo Village, especially the Karya Tani Farmer Group, which is a service partner, is the unavailability of water to irrigate rice fields during the dry season. This unavailability of water causes a reduction in the productivity of farmers who are supposed to harvest three times to only twice a year. Through community service activities carried out the construction of borehole irrigation in Sembirejo Village. This method utilizes ground water as a source of water supply during the dry season. Drilled well irrigation can be enjoyed directly by farmers in the vicinity of the service area, and in the dry season the water needs for plants are available.